Romania in the Context of Globalization, Regionalization and Convergence - Elena Pelinescu (Romanian Journal of European Affairs, 2007)
The economic convergence is an instrument of harmonization in areas with high degree of economic integration. For Romania, it is important to know the degree of fulfillment of the convergence criteria and the impact of the policies which sustain their achievement, because few studies had as object the analysis of the degree of fulfillment in countries like Romania and Bulgaria, which were included in the latest EU extension wave. We use different methods in order to show the cointegration process and the results. The techniques applied to the statistical data regarding the nominal convergence (the consolidated budget deficit as a share of GDP, the share of public debt in GDP, the rate of inflation, the interest rate and the exchange rate) have revealed some results which appear in others studies too, namely that Romania integrates in the fixed target Maastricht criteria (the budget deficit as a share of GDP, the share of public debt in GDP) and follows a pattern of convergence for the other criteria.